Maturity models for business continuity–A systematic literature review - Pinto, D. (2022)
Business continuity refers to the planning and preparation done ahead of time to ensure that an organization's essential business processes can continue to work in the event of an emergency. Natural disasters, business crises, pandemics, workplace crime, or any other incident that disrupts business operations are examples of emergencies. Maturity models provide companies with a way to assess their relative implementation for a management framework. This paper provides a Process Assessment Model for Business Continuity based on a Systematic Literature Review. The selected articles from the literature provide information about the state-of-the-art in this research field, an understanding of the numerous research activities that have been undertaken in recent years, and a forecast of potential developments.